Monetary policy transmission mechanism nexus economic growth: evidence from Botswana - Kootsholetse, Neo (Graduate School of Business (GSB), 2023)
Since its inception, monetary policy has been used as a tool to help achieve periodic quantitative targets for monetary aggregates that have been established. It is only recently that developing countries have taken a more modern strategy to achieving their inflation objectives by utilizing policy rates. Several factors have contributed to this phenomenon, including the weak link between money and inflation, global financial integration, greater exchange rate flexibility, lower fiscal financing requirements for governments, and the liberalization of financial markets, all of which have contributed to, or have perpetuated, instability in money demand. The primary goal of the research is examining the influence of monetary policy transmission on Botswana's economic growth. Data was sourced from Botswana's Statistics Office and the World Bank database in which annual time series data from 1980 to 2018 was collated and analysed. In determining the stationarity of the variables utilized in the study, the Augmented Dickey-Fuller (ADF) unit root test was applied. The presence of long-run correlations among the variables in the study was assessed using the Autoregressive Distributed Lag (ARDL) bounds test to cointegration. Only estimates for the short-run relationship are considered because the ARDL bounds tests revealed no long-term correlations between the variables. The Vector Autoregressive (VAR) found a significant unidirectional short-run causal association between gross fixed capital formation (GFCF) and real gross domestic product (GDP), as well as a significant unidirectional short-run causal relationship between bank rate and GFCF in the short term. Even though the study's findings demonstrated that the variables had a causal relationship, it was expected that there would be more linkages between them. This study recommends the need for structural changes in Botswana's economy in order for adjustments in the monetary policy rate to have the desired effect on the economy. The study further suggests that monetary policy be used to foster an investment climate that attracts both domestic and foreign capital, so encouraging long-term economic growth